Perceptual Encoding of Natural Speech Sounds Revealed by the N1 Event-Related Potential Response. Issue 1 (3rd April 2018) - Pereira, Olivia; Gao, Yang Agnes; Toscano, Joseph C.
ABSTRACT: Recent work has demonstrated that the auditory N1 event-related potential (ERP) component tracks continuous changes in voice onset time (an acoustic cue distinguishing word-initial voicing categories), suggesting that this ERP response can index early perceptual representations. The present study aims to determine whether the N1 can serve as a more general index of cue encoding, providing a tool for measuring listeners' perception of fine-grained acoustic diﬀerences in speech. We examined ERP responses to a wide range of phonetic contrasts, focusing particularly on voicing and place of articulation distinctions for diﬀerent classes of speech sounds. Listeners were presented with natural speech spanning 18 consonants in English, and identified the consonant they heard while electroencephalograph (EEG) was recorded. Results show diﬀerences in N1 amplitude as a function of voicing and place for both fricatives and stop consonants, replicating and extending previous findings. The pattern of results also suggests that some distinctions reflect perceptual encoding based on acoustic cue dimensions rather than articulatory dimensions. Overall, these results demonstrate that the N1 can serve as a general index of perceptual encoding at early stages of auditory perception across a range of phonetic contrasts in speech.